Decks Serve as Classrooms for Maritime Academy - Long Beach Press Telegram (Long Beach Press Telegram)
Returning from a two months' southern cruise, the S. S. California State, California Maritime Academy training ship, docked at 10 a. m. today in Long Beach Harbor for a five-day visit before continuing to her base at San Francisco.